Effectiveness of Online Learning In Pandemic Covid-19 - Bahasoan , Awal Nopriyanto; Wulan Ayuandiani; Muhammad Mukhram; Aswar Rahmat (International Journal of Science, Technology & Management, 2020)
This study aims to determine the effectiveness of online learning during the Covid-19 pandemic. This research is a quantitative descriptive study using survey methods conducted online. The sample collection method uses simple random sampling, where the sample of this study is an active student in the management study program, Faculty of Economics, University of West Sulawesi; Primary data collection in this study was carried out by distributing questionnaires online to 115 respondents. Data obtained by filling out questions that were distributed to all respondents in the form of Google on the link https://forms.gle/VbqM7myWhwdfpMfc9. Furthermore, the collected data was analyzed to be described. The results of data analysis obtained from filling student questionnaires can be concluded that the online learning system carried out during the COVID-19 pandemic is effective and inefficient. Effectively implemented because of the conditions that require online study and inefficient because the costs incurred more when compared with offline lectures.